Electromagnetic shielding fabric and preparation method thereof
Polycarbazole coated magnesium hydroxide and phosphorus-containing flame retardant monomer is added to polymerize tetramethyldivinyldisiloxane and phosphorus-containing flame retardant monomer to obtain phosphorus silicon synergistic flame retardant, and polycarbazole coated magnesium hydroxide is oxidized and polymerized and deposited on the surface of magnesium hydroxide to produce polycarbazole coated magnesium hydroxide, and phosphorus silicon synergistic flame retardant are then prepared into spinning liquid, and wet spinning is used to produce polystyrene hollow fibers, and finally textile it into an electromagnetic shielding fabric, solving the problem of traditional clothing fabrics lacking electromagnetic shielding performance, achieving efficient electromagnetic wave isolation and excellent flame retardant and antibacterial properties.
Patent Information
- Application Number
- CN202510232916.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-28
- Publication Date
- 2025-05-30
AI Technical Summary
Traditional clothing fabrics lack good electromagnetic shielding performance and cannot effectively block electromagnetic waves, resulting in harm to human health.
A method of preparing electromagnetic shielding fabric is adopted to prepare a phospho-silicon co-effective flame retardant by adding polymerization of tetramethyldivinyldisiloxane with phosphorus-containing flame retardant monomer, and oxidative polymerization of carbazole and N-vinylcarbazole and depositing it on the surface of magnesium hydroxide to obtain polycarbazole coated magnesium hydroxide. Then, modified polystyrene, polycarbazole coated magnesium hydroxide, and phosphorus-silicon co-effective flame retardant are prepared into a spinning liquid, and wet spinning to produce polystyrene hollow fibers, and finally textile into an electromagnetic shielding fabric.
This electromagnetic shielding fabric has excellent flame retardant properties, antibacterial properties and electromagnetic shielding properties, which can effectively isolate electromagnetic waves and protect human health.
Smart Images

Figure BDA0005291995090000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of textile fabrics, and specifically to an electromagnetic shielding fabric and a preparation method thereof. Background Art
[0002] The rapid development of the Internet of Things has promoted the upgrading of electronic devices, making them gradually develop towards multi-functionality and intelligence. While people enjoy the convenience brought by flexible electronic devices, they are constantly exposed to electromagnetic wave radiation. Nowadays, electromagnetic pollution has become the fourth major pollution after water pollution, air pollution, and noise pollution. It can damage human health, interfere with the operation of equipment, and even leak private information, threatening the information security of countries and enterprises. The interference of electromagnetic radiation on human health is particularly prominent. The energy carried by electromagnetic waves is absorbed by the human body and converted into heat, causing the temperature of human tissues to rise. When the frequency of electromagnetic radiation is low, it will damage the eyes, causing eyelid swelling or eye congestion in a short time and cataracts in the long term. When the frequency of electromagnetic radiation is high, the wavelength is short and the skin depth is shallow, and heat is generated on the body surface or under the skin, resulting in skin fever and itching. Moreover, electromagnetic radiation will disrupt the rhythm and frequency of the brain's nerve discharge. The human body will experience dizziness and headache symptoms under short-term radiation, and long-term radiation will increase the probability of suffering from Alzheimer's disease and Parkinson's disease.
[0003] Clothing is the most direct and convenient way for people to resist external environmental interference. However, traditional clothing fabrics do not have good electromagnetic shielding performance, which far fails to meet the needs of protecting human health for workers who are long-term exposed to electromagnetic environments. Therefore, it is necessary to propose an electromagnetic shielding fabric, which has great and far-reaching significance for effectively blocking electromagnetic waves and protecting human health. Summary of the Invention
[0004] Aiming at the deficiencies of the prior art, the technical problem to be solved by the present invention is to provide an electromagnetic shielding fabric and a preparation method thereof.
[0005] The technical solution of the present invention to solve the above-mentioned fabric technical problem is to provide an electromagnetic shielding fabric. The electromagnetic shielding fabric is prepared by adding and polymerizing tetramethyldivinyldisiloxane and a phosphorus-containing flame retardant monomer to obtain a phosphorus-silicon synergistic flame retardant; oxidatively polymerizing and depositing carbazole and N-vinylcarbazole on the surface of magnesium hydroxide to obtain polycarbazole-coated magnesium hydroxide; reacting pre-modified polystyrene and an organotin antibacterial agent to obtain modified polystyrene; formulating a spinning solution with the modified polystyrene, polycarbazole-coated magnesium hydroxide, and phosphorus-silicon synergistic flame retardant, and wet spinning to obtain polystyrene hollow fibers; and then weaving the polystyrene hollow fibers into an electromagnetic shielding fabric.
[0006] The phosphorus-containing flame retardant monomer is prepared by reacting 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide with formic acid;
[0007] The organotin antibacterial agent is prepared by reacting salicylaldehyde tyrosine Schiff base ligand with dimethyltin dichloride;
[0008] The salicylaldehyde tyrosine Schiff base ligand is prepared by reacting 3-allyl-2-hydroxybenzaldehyde with tyrosine;
[0009] The pre-modified polystyrene is prepared by reacting polystyrene with chloromethyl methyl ether.
[0010] The technical solution for the present invention to solve the technical problem of the method is to provide a preparation method of an electromagnetic shielding fabric, including the following preparation steps:
[0011] (1) Tetramethyldivinyldisiloxane and the phosphorus-containing flame retardant monomer are added to N,N-dimethylformamide which is 10 - 12 times the mass of tetramethyldivinyldisiloxane at a molar ratio of 1:(1.1 - 1.3). Under nitrogen protection, stir and react at 60 - 70 °C and 300 - 500 r / min for 10 - 12 h, and dry at 50 - 60 °C under vacuum for 7 - 9 h to obtain a phosphorus-silicon synergistic flame retardant;
[0012] (2) Magnesium hydroxide, anhydrous ferric chloride, and dichloromethane are mixed evenly at a mass ratio of 1:(2 - 3):(20 - 30) to prepare a mixed reaction solution; carbazole and N-vinylcarbazole are added to dichloromethane which is 8 - 10 times the mass of carbazole at a molar ratio of 1:(0.2 - 0.3) and mixed evenly to prepare a carbazole monomer solution; under stirring conditions at 20 - 30 °C and 300 - 500 r / min, the carbazole monomer solution which is 0.4 - 0.6 times the mass of the mixed reaction solution is added dropwise to the mixed reaction solution at a uniform speed within 30 min, and continue to stir and react for 20 - 24 h, and dry at 50 - 60 °C under vacuum for 7 - 9 h to obtain polycarbazole-coated magnesium hydroxide;
[0013] (3) Dimethyltin dichloride and methanol are mixed evenly at a mass ratio of 1:(4 - 6) to prepare a dimethyltin dichloride solution; dimethyltin dichloride, an equimolar amount of salicylaldehyde tyrosine Schiff base ligand, triethylamine, and methanol are mixed evenly at a mass ratio of 1:(0.03 - 0.05):(8 - 10). Under nitrogen protection, stir at 50 - 60 °C and 300 - 500 r / min, and add the dimethyltin dichloride solution dropwise at a uniform speed within 10 min, and continue to stir and react for 1 - 2 h, and dry at 50 - 60 °C under vacuum for 7 - 9 h to obtain the organotin antibacterial agent;
[0014] (4) Mix pre-modified polystyrene, organotin antibacterial agent, potassium carbonate, and N,N-dimethylformamide evenly according to a mass ratio of 1:(0.2 - 0.3):(0.02 - 0.04):(10 - 12), stir and react at 55 - 65°C and 300 - 500 r / min for 2 - 3 h, and dry at 50 - 60°C for 8 - 10 h under vacuum conditions to obtain modified polystyrene;
[0015] (5) Mix modified polystyrene, polycarbazole-coated magnesium hydroxide, phosphorus-silicon synergistic flame retardant, chloroplatinic acid, and N,N-dimethylformamide evenly according to a mass ratio of 1:(0.04 - 0.06):(0.06 - 0.08):(0.001 - 0.002):(6 - 7), stir at 10 - 30°C and 300 - 500 r / min for 10 - 20 min to prepare a spinning solution; perform wet spinning on the spinning solution to obtain nascent fibers, let the nascent fibers stand at 70 - 80°C for 2 - 3 h under vacuum conditions, and dry at 50 - 60°C for 6 - 8 h to obtain polystyrene hollow fibers; weave the polystyrene hollow fibers into an electromagnetic shielding fabric through a textile machine.
[0016] As an optimization, the preparation method of the phosphorus-containing flame retardant monomer described in step (1) is: Mix 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and chloroform evenly according to a mass ratio of 1:(10 - 12), under nitrogen protection, at 20 - 40°C and under stirring conditions of 300 - 500 r / min, dropwise add formic acid twice the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide evenly within 30 min, continue stirring and reacting for 30 - 40 min, and dry at 50 - 60°C for 6 - 8 h under vacuum conditions to obtain the phosphorus-containing flame retardant monomer.
[0017] As an optimization, the particle size of the magnesium hydroxide described in step (2) is 1 - 2 μm.
[0018] As an optimization, the preparation method of the salicylaldehyde tyrosine Schiff base ligand described in step (3) is: Mix 3-allyl-2-hydroxybenzaldehyde and methanol evenly according to a mass ratio of 1:(4 - 6) to prepare a 3-allyl-2-hydroxybenzaldehyde solution; add tyrosine and potassium hydroxide in an equimolar amount of 3-allyl-2-hydroxybenzaldehyde to methanol 10 - 12 times the mass of tyrosine according to a molar ratio of 1:1, stir at 50 - 60°C and 300 - 500 r / min for 8 - 12 min, under nitrogen protection, at 50 - 60°C and under stirring conditions of 300 - 500 r / min, dropwise add the 3-allyl-2-hydroxybenzaldehyde solution evenly within 15 min, continue stirring and reacting for 2 - 3 h, and dry at 50 - 60°C for 7 - 9 h under vacuum conditions to obtain the salicylaldehyde tyrosine Schiff base ligand.
[0019] As an optimization, the preparation method of the pre-modified polystyrene described in step (4) is as follows: Mix polystyrene, chloromethyl methyl ether, stannic chloride, and N,N-dimethylformamide in a mass ratio of 1:(0.2 - 0.3):(0.03 - 0.05):(10 - 12) evenly, stir and react at 30 - 40 °C and 300 - 500 r / min for 4 - 6 h, and dry at 50 - 60 °C for 8 - 10 h under vacuum conditions to obtain the pre-modified polystyrene.
[0020] As an optimization, the molecular weight of the polystyrene is 90,000 - 100,000.
[0021] As an optimization, the technological process of the wet spinning in step (5) is as follows: Immerse the spinneret in deionized water, pour the spinning solution into the liquid container for wet spinning, and convey the spinning solution in the liquid container to the spinneret assembly through a peristaltic pump, with a conveying speed of 0.58 - 0.62 mL / min. The outer diameter of the spinneret holes on the spinneret is 1.3 - 1.5 mm, and the inner diameter is 0.6 - 0.8 mm. After the spinning solution is extruded through the spinneret holes, a hollow spun fiber stream is formed. At the same time, another peristaltic pump conveys deionized water into the inside of the hollow spun fiber stream, with a conveying speed of 0.8 - 1 mL / min. The inner and outer surfaces of the hollow spun fiber stream come into contact with deionized water simultaneously, and under the action of double diffusion, the hollow spun fiber stream solidifies into primary fibers.
[0022] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0023] When preparing the electromagnetic shielding fabric, the present invention reacts 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide with formic acid to obtain a phosphorus-containing flame retardant monomer; adds and polymerizes tetramethyldivinyldisiloxane with the phosphorus-containing flame retardant monomer to obtain a phosphorus-silicon synergistic flame retardant; oxidatively polymerizes carbazole and N-vinylcarbazole and deposits them on the surface of magnesium hydroxide to obtain polycarbazole-coated magnesium hydroxide; reacts 3-allyl-2-hydroxybenzaldehyde with tyrosine to obtain a salicylaldehyde tyrosine Schiff base ligand; reacts the salicylaldehyde tyrosine Schiff base ligand with dimethyltin dichloride to obtain an organotin antibacterial agent; reacts polystyrene with chloromethyl methyl ether to obtain pre-modified polystyrene; reacts the pre-modified polystyrene with the organotin antibacterial agent to obtain modified polystyrene; formulates a spinning solution with the modified polystyrene, polycarbazole-coated magnesium hydroxide, and phosphorus-silicon synergistic flame retardant, and prepares polystyrene hollow fibers by wet spinning; and then weaves the polystyrene hollow fibers into an electromagnetic shielding fabric.
[0024] First, react 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide with formic acid to prepare a phosphorus-containing flame retardant monomer, and introduce P-H bonds at both ends of the phosphorus-containing flame retardant monomer; carry out a phosphine-hydrogen addition reaction between the carbon-carbon double bond on tetramethyldivinyldisiloxane and the P-H bond on the phosphorus-containing flame retardant monomer to prepare a phosphorus-silicon synergistic flame retardant. Keep the phosphorus-containing flame retardant monomer in excess so that both ends of the phosphorus-silicon synergistic flame retardant are capped with the phosphorus-containing flame retardant monomer, and introduce P-H bonds at both ends of the phosphorus-silicon synergistic flame retardant; phosphorus elements can capture free radicals, promote the formation of a carbon layer to isolate heat and oxygen, and endow the electromagnetic shielding fabric with excellent flame retardant properties; the bond energy of the Si-O bond is greater than that of the C-C bond. Therefore, compared with the C-C bond, the Si-O bond needs to absorb more heat and its own vibration energy to resolve the energy for the thermal decomposition of the polymer material. The layered SiO formed by the degradation of the siloxane during combustion migrates to the surface of the carbon layer, making the carbon layer more dense, inhibiting the oxidation of the carbon layer, enhancing the stability of the carbon layer at high temperatures, and further improving the flame retardant properties of the electromagnetic shielding fabric; the P-H bonds introduced at both ends of the phosphorus-silicon synergistic flame retardant can undergo a phosphine-hydrogen addition reaction with the carbon-carbon double bonds on polycarbazole-coated magnesium hydroxide and modified polystyrene to form a crosslinked network, inhibit the relative slippage between molecular chains, and endow the electromagnetic shielding fabric with excellent mechanical properties. 2 Migrate to the surface of the carbon layer, making the carbon layer more dense, inhibiting the oxidation of the carbon layer, enhancing the stability of the carbon layer at high temperatures, and further improving the flame retardant properties of the electromagnetic shielding fabric; the P-H bonds introduced at both ends of the phosphorus-silicon synergistic flame retardant can undergo a phosphine-hydrogen addition reaction with the carbon-carbon double bonds on polycarbazole-coated magnesium hydroxide and modified polystyrene to form a crosslinked network, inhibit the relative slippage between molecular chains, and endow the electromagnetic shielding fabric with excellent mechanical properties.
[0025] Secondly, oxidatively polymerize carbazole and N-vinylcarbazole and deposit them on the surface of magnesium hydroxide to prepare polycarbazole-coated magnesium hydroxide; and introduce carbon-carbon double bonds on the surface of polycarbazole-coated magnesium hydroxide; polycarbazole is a conductive polymer material that can form a conductive path in the electromagnetic shielding fabric and endow the electromagnetic shielding fabric with excellent electromagnetic shielding properties; magnesium hydroxide has an endothermic effect. When magnesium hydroxide is heated by a heat source, it will undergo a dehydration reaction to generate water vapor and magnesium oxide. This is an endothermic reaction that absorbs a large amount of heat. Magnesium oxide will react with the carbide on the surface of the combustible to form a stable carbide layer. This carbide layer has good heat insulation performance and can prevent the combustible from contacting with oxygen in the outside world. Modify the surface of magnesium hydroxide to improve the compatibility between magnesium hydroxide and the matrix resin, make magnesium hydroxide not easily agglomerate in the group resin, and disperse evenly, further improving the flame retardant properties of the electromagnetic shielding fabric; the carbon-carbon double bonds introduced on the surface of polycarbazole-coated magnesium hydroxide can undergo an addition reaction with the P-H bonds introduced at both ends of the phosphorus-silicon synergistic flame retardant to form a crosslinked network, inhibit the relative slippage between molecular chains, and endow the electromagnetic shielding fabric with excellent mechanical properties.
[0026] Finally, salicylaldehyde tyrosine Schiff base ligand was prepared by reacting 3 - allyl - 2 - hydroxybenzaldehyde with tyrosine; an organotin antibacterial agent was prepared by reacting salicylaldehyde tyrosine Schiff base ligand with dimethyltin dichloride, and a hydroxyl group and a carbon - carbon double bond were introduced at both ends of the organotin antibacterial agent respectively; pre - modified polystyrene was prepared by reacting polystyrene with chloromethyl methyl ether, the benzene ring part of polystyrene was chloromethylated, chlorine atoms were introduced on the side chain of polystyrene, and the chlorine atoms on the pre - modified polystyrene were reacted with the hydroxyl groups on the organotin antibacterial agent to obtain modified polystyrene; the organotin antibacterial agent was grafted on the side chain of the modified polystyrene, and a carbon - carbon double bond was introduced; the organotin complex on the organotin antibacterial agent could well inhibit the biological activity of bacteria, endowing the electromagnetic shielding fabric with excellent antibacterial properties; the carbon - carbon double bond on the side chain of the modified polystyrene could undergo an addition reaction with the P - H bonds introduced at both ends of the phosphorus - silicon synergistic flame retardant to form a cross - linked network, inhibiting the relative slippage between molecular chains and endowing the electromagnetic shielding fabric with excellent mechanical properties; the modified polystyrene, polycarbazole - coated magnesium hydroxide, and phosphorus - silicon synergistic flame retardant were formulated into a spinning solution, and wet spinning was used to prepare polystyrene hollow fibers; then the polystyrene hollow fibers were woven into an electromagnetic shielding fabric; the hollow porous structure could increase the specific surface area of the electromagnetic shielding fabric, expand the propagation path of electromagnetic waves, and induce multiple reflections and scattering of electromagnetic waves inside the electromagnetic shielding fabric, further enhancing the electromagnetic shielding performance of the electromagnetic shielding fabric. Detailed implementation manners
[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0028] Example 1
[0029] A preparation method of an electromagnetic shielding fabric, the preparation method of the electromagnetic shielding fabric includes the following preparation steps:
[0030] (1) Mix 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and chloroform in a mass ratio of 1:10 evenly. Under nitrogen protection, at 20 °C and with stirring at 30 r / min, dropwise add formic acid twice the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide evenly within 30 min. Continue stirring and reacting for 40 min. Under vacuum conditions, dry at 50 °C for 8 h to obtain a phosphorus-containing flame retardant monomer; Add tetramethyldivinyldisiloxane and the phosphorus-containing flame retardant monomer in a molar ratio of 1:1.1 to N,N-dimethylformamide 10 times the mass of tetramethyldivinyldisiloxane. Under nitrogen protection, react with stirring at 60 °C and 300 r / min for 12 h. Under vacuum conditions, dry at 50 °C for 9 h to obtain a phosphorus-silicon synergistic flame retardant;
[0031] (2) Mix magnesium hydroxide, anhydrous ferric chloride, and dichloromethane in a mass ratio of 1:2:20 evenly to prepare a mixed reaction solution; Add carbazole and N-vinylcarbazole in a molar ratio of 1:0.2 to dichloromethane 8 times the mass of carbazole and mix evenly to prepare a carbazole monomer solution; Under stirring conditions at 20 °C and 300 r / min, dropwise add the carbazole monomer solution 0.4 times the mass of the mixed reaction solution evenly to the mixed reaction solution within 30 min. Continue stirring and reacting for 24 h. Under vacuum conditions, dry at 50 °C for 9 h to obtain polycarbazole-coated magnesium hydroxide;
[0032] (3) Mix 3-allyl-2-hydroxybenzaldehyde and methanol in a mass ratio of 1:4 evenly to prepare a 3-allyl-2-hydroxybenzaldehyde solution; Add 3-allyl-2-hydroxybenzaldehyde, tyrosine, and potassium hydroxide in an equimolar ratio in a molar ratio of 1:1 to methanol 10 times the mass of tyrosine. Stir at 50 °C and 300 r / min for 12 min. Under nitrogen protection, under stirring conditions at 50 °C and 300 r / min, dropwise add the 3-allyl-2-hydroxybenzaldehyde solution evenly within 15 min. Continue stirring and reacting for 3 h. Under vacuum conditions, dry at 50 °C for 9 h to obtain a salicylaldehyde tyrosine Schiff base ligand; Mix dimethyltin dichloride and methanol in a mass ratio of 1:4 evenly to prepare a dimethyltin dichloride solution; Add dimethyltin dichloride, the salicylaldehyde tyrosine Schiff base ligand, triethylamine, and methanol in an equimolar ratio in a mass ratio of 1:0.03:8 and mix evenly. Under nitrogen protection, under stirring conditions at 50 °C and 300 r / min, dropwise add the dimethyltin dichloride solution evenly within 10 min. Continue stirring and reacting for 2 h. Under vacuum conditions, dry at 50 °C for 9 h to obtain an organotin antibacterial agent;
[0033] (4) Mix polystyrene, chloromethyl methyl ether, tin tetrachloride, and N,N-dimethylformamide evenly according to a mass ratio of 1:0.2:0.03:10. Stir and react at 30 °C and 300 r / min for 6 h, and dry at 50 °C for 10 h under vacuum conditions to obtain pre-modified polystyrene; mix pre-modified polystyrene, organotin antibacterial agent, potassium carbonate, and N,N-dimethylformamide evenly according to a mass ratio of 1:0.2:0.02:10. Stir and react at 55 °C and 300 r / min for 3 h, and dry at 50 °C for 10 h under vacuum conditions to obtain modified polystyrene;
[0034] (5) Mix modified polystyrene, polycarbazole-coated magnesium hydroxide, phosphorus-silicon synergistic flame retardant, chloroplatinic acid, and N,N-dimethylformamide evenly according to a mass ratio of 1:0.04:0.06:0.001:6. Stir at 10 °C and 300 r / min for 20 min to prepare a spinning solution; immerse the spinneret in deionized water, pour the spinning solution into the liquid container for wet spinning, and use a peristaltic pump to transport the spinning solution in the liquid container to the spinneret assembly at a transport speed of 0.58 mL / min. The outer diameter of the spinneret holes on the spinneret is 1.3 mm, and the inner diameter is 0.6 mm. After the spinning solution is extruded through the spinneret holes, it forms a hollow spinning filament. At the same time, another peristaltic pump transports deionized water into the inside of the hollow spinning filament at a transport speed of 0.8 mL / min. The inner and outer surfaces of the hollow spinning filament come into contact with deionized water at the same time. Under the action of double diffusion, the hollow spinning filament solidifies into a primary fiber. Leave the primary fiber standing at 70 °C for 3 h under vacuum conditions and dry at 50 °C for 8 h to obtain polystyrene hollow fibers; weave the polystyrene hollow fibers into an electromagnetic shielding fabric through a textile machine.
[0035] Example 2
[0036] A preparation method of an electromagnetic shielding fabric, the preparation method of the electromagnetic shielding fabric includes the following preparation steps:
[0037] (1) Mix 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and chloroform in a mass ratio of 1:11 evenly. Under nitrogen protection, at 30 °C and with stirring at 400 r / min, dropwise add formic acid twice the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide evenly within 30 min. Continue stirring and reacting for 35 min, and dry at 55 °C for 7 h under vacuum conditions to obtain a phosphorus-containing flame retardant monomer; Add tetramethyldivinyldisiloxane and the phosphorus-containing flame retardant monomer in a molar ratio of 1:1.2 to N,N-dimethylformamide 11 times the mass of tetramethyldivinyldisiloxane. Under nitrogen protection, react with stirring at 65 °C and 400 r / min for 11 h, and dry at 55 °C for 8 h under vacuum conditions to obtain a phosphorus-silicon synergistic flame retardant;
[0038] (2) Mix magnesium hydroxide, anhydrous ferric chloride, and dichloromethane in a mass ratio of 1:2.5:25 evenly to prepare a mixed reaction solution; Add carbazole and N-vinylcarbazole in a molar ratio of 1:0.25 to dichloromethane 9 times the mass of carbazole and mix evenly to prepare a carbazole monomer solution; Under stirring conditions at 25 °C and 400 r / min, dropwise add the carbazole monomer solution 0.5 times the mass of the mixed reaction solution evenly to the mixed reaction solution within 30 min. Continue stirring and reacting for 22 h, and dry at 55 °C for 8 h under vacuum conditions to obtain polycarbazole-coated magnesium hydroxide;
[0039] (3) Mix 3-allyl-2-hydroxybenzaldehyde and methanol in a mass ratio of 1:5 evenly to prepare a 3-allyl-2-hydroxybenzaldehyde solution; Add tyrosine and potassium hydroxide in an equimolar amount to 3-allyl-2-hydroxybenzaldehyde in a molar ratio of 1:1 to methanol 11 times the mass of tyrosine, stir at 55 °C and 400 r / min for 10 min. Under nitrogen protection, under stirring conditions at 55 °C and 400 r / min, dropwise add the 3-allyl-2-hydroxybenzaldehyde solution evenly within 15 min. Continue stirring and reacting for 2.5 h, and dry at 55 °C for 8 h under vacuum conditions to obtain a salicylaldehyde tyrosine Schiff base ligand; Mix dimethyltin dichloride and methanol in a mass ratio of 1:5 evenly to prepare a dimethyltin dichloride solution; Mix dimethyltin dichloride, the salicylaldehyde tyrosine Schiff base ligand, triethylamine, and methanol in an equimolar amount in a mass ratio of 1:0.04:9 evenly. Under nitrogen protection, under stirring conditions at 55 °C and 400 r / min, dropwise add the dimethyltin dichloride solution evenly within 10 min. Continue stirring and reacting for 1.5 h, and dry at 55 °C for 8 h under vacuum conditions to obtain an organotin antibacterial agent;
[0040] (4) Mix polystyrene, chloromethyl methyl ether, tin tetrachloride, and N,N-dimethylformamide evenly according to a mass ratio of 1:0.25:0.04:11, stir and react at 35 °C and 400 r / min for 5 h, and dry at 55 °C for 9 h under vacuum conditions to obtain pre-modified polystyrene; mix pre-modified polystyrene, organotin antibacterial agent, potassium carbonate, and N,N-dimethylformamide evenly according to a mass ratio of 1:0.25:0.03:11, stir and react at 60 °C and 400 r / min for 2.5 h, and dry at 55 °C for 9 h under vacuum conditions to obtain modified polystyrene;
[0041] (5) Mix modified polystyrene, polycarbazole-coated magnesium hydroxide, phosphorus-silicon synergistic flame retardant, chloroplatinic acid, and N,N-dimethylformamide evenly according to a mass ratio of 1:0.05:0.07:0.0015:6.5, stir at 20 °C and 400 r / min for 15 min to prepare a spinning solution; immerse the spinneret in deionized water, pour the spinning solution into the liquid container for wet spinning, and use a peristaltic pump to transport the spinning solution in the liquid container to the spinneret assembly at a transport speed of 0.6 mL / min. The outer diameter of the spinneret holes on the spinneret is 1.4 mm, and the inner diameter is 0.7 mm. After the spinning solution is extruded through the spinneret holes, it forms a hollow spinning filament. At the same time, another peristaltic pump transports deionized water into the inner part of the hollow spinning filament at a transport speed of 0.9 mL / min. The inner and outer surfaces of the hollow spinning filament come into contact with deionized water simultaneously. Under the action of double diffusion, the hollow spinning filament solidifies into a primary fiber. Let the primary fiber stand at 75 °C for 2.5 h under vacuum conditions and dry at 55 °C for 7 h to obtain polystyrene hollow fibers; weave the polystyrene hollow fibers into an electromagnetic shielding fabric through a textile machine.
[0042] Example 3
[0043] A preparation method of an electromagnetic shielding fabric, the preparation method of the electromagnetic shielding fabric includes the following preparation steps:
[0044] (1) Mix 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and chloroform evenly at a mass ratio of 1:12. Under nitrogen protection, at 40 °C and with stirring at 500 r / min, dropwise add formic acid which is twice the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide evenly within 30 min. Continue stirring and reacting for 30 min, and then dry at 60 °C for 6 h under vacuum conditions to obtain a phosphorus-containing flame retardant monomer. Add tetramethyldivinyldisiloxane and the phosphorus-containing flame retardant monomer to N,N-dimethylformamide which is 12 times the mass of tetramethyldivinyldisiloxane at a molar ratio of 1:1.3. Under nitrogen protection, react with stirring at 70 °C and 500 r / min for 10 h, and then dry at 60 °C for 7 h under vacuum conditions to obtain a phosphorus-silicon synergistic flame retardant;
[0045] (2) Mix magnesium hydroxide, anhydrous ferric chloride, and dichloromethane evenly at a mass ratio of 1:3:30 to prepare a mixed reaction solution. Add carbazole and N-vinylcarbazole to dichloromethane which is 10 times the mass of carbazole at a molar ratio of 1:0.3 and mix evenly to prepare a carbazole monomer solution. Under stirring conditions at 30 °C and 500 r / min, dropwise add the carbazole monomer solution which is 0.6 times the mass of the mixed reaction solution evenly into the mixed reaction solution within 30 min. Continue stirring and reacting for 20 h, and then dry at 60 °C for 7 h under vacuum conditions to obtain polycarbazole-coated magnesium hydroxide;
[0046] (3) Mix 3-allyl-2-hydroxybenzaldehyde and methanol evenly at a mass ratio of 1:6 to prepare a 3-allyl-2-hydroxybenzaldehyde solution. Add 3-allyl-2-hydroxybenzaldehyde, tyrosine, and potassium hydroxide in equimolar amounts to methanol which is 12 times the mass of tyrosine at a molar ratio of 1:1. Stir at 60 °C and 500 r / min for 8 min. Under nitrogen protection and stirring conditions at 60 °C and 500 r / min, dropwise add the 3-allyl-2-hydroxybenzaldehyde solution evenly within 15 min. Continue stirring and reacting for 2 h, and then dry at 60 °C for 7 h under vacuum conditions to obtain a salicylaldehyde tyrosine Schiff base ligand. Mix dimethyltin dichloride and methanol evenly at a mass ratio of 1:6 to prepare a dimethyltin dichloride solution. Mix dimethyltin dichloride, the salicylaldehyde tyrosine Schiff base ligand, triethylamine, and methanol in equimolar amounts at a mass ratio of 1:0.05:10. Under nitrogen protection and stirring conditions at 60 °C and 500 r / min, dropwise add the dimethyltin dichloride solution evenly within 10 min. Continue stirring and reacting for 1 h, and then dry at 60 °C for 7 h under vacuum conditions to obtain an organotin antibacterial agent;
[0047] (4) Mix polystyrene, chloromethyl methyl ether, tin tetrachloride, and N,N-dimethylformamide evenly at a mass ratio of 1:0.3:0.05:12, stir and react at 40 °C and 500 r / min for 4 h, and dry at 60 °C for 8 h under vacuum conditions to obtain pre-modified polystyrene; Mix pre-modified polystyrene, organotin antibacterial agent, potassium carbonate, and N,N-dimethylformamide evenly at a mass ratio of 1:0.3:0.04:12, stir and react at 65 °C and 500 r / min for 2 h, and dry at 60 °C for 8 h under vacuum conditions to obtain modified polystyrene;
[0048] (5) Mix modified polystyrene, polycarbazole-coated magnesium hydroxide, phosphorus-silicon synergistic flame retardant, chloroplatinic acid, and N,N-dimethylformamide evenly at a mass ratio of 1:0.06:0.08:0.002:7, stir at 30 °C and 500 r / min for 10 min to prepare a spinning solution; Immerse the spinneret in deionized water, pour the spinning solution into the liquid container for wet spinning, and use a peristaltic pump to transport the spinning solution in the liquid container to the spinneret assembly at a transport speed of 0.62 mL / min. The outer diameter of the spinneret holes on the spinneret is 1.5 mm, and the inner diameter is 0.8 mm. After the spinning solution is extruded through the spinneret holes, it forms a hollow spinning fine stream. At the same time, another peristaltic pump transports deionized water into the hollow spinning fine stream at a transport speed of 1 mL / min. The inner and outer surfaces of the hollow spinning fine stream come into contact with deionized water simultaneously. Under the action of double diffusion, the hollow spinning fine stream solidifies into primary fibers. Let the primary fibers stand at 80 °C for 2 h under vacuum conditions and dry at 60 °C for 6 h to obtain polystyrene hollow fibers; Weave the polystyrene hollow fibers into an electromagnetic shielding fabric through a textile machine.
[0049] Comparative Example 1
[0050] The preparation method of the electromagnetic shielding fabric of Comparative Example 1 is different from that of Example 2 in that step (1) is not carried out, and step (5) is modified as follows: Modify polystyrene, magnesium hydroxide coated with polycarbazole, chloroplatinic acid, and N,N-dimethylformamide are mixed evenly according to a mass ratio of 1:0.05:0.0015:6.5, stirred at 20 °C and 400 r / min for 15 min to prepare a spinning solution; the spinneret is immersed in deionized water, the spinning solution is poured into the liquid container for wet spinning, and the spinning solution in the liquid container is transported to the spinneret assembly through a peristaltic pump at a transport speed of 0.6 mL / min. The outer diameter of the spinneret holes on the spinneret is 1.4 mm, and the inner diameter is 0.7 mm. After the spinning solution is extruded through the spinneret holes, a hollow spinning filament is formed. At the same time, another peristaltic pump transports deionized water into the hollow spinning filament at a transport speed of 0.9 mL / min. The inner and outer surfaces of the hollow spinning filament are in contact with deionized water at the same time. Under the action of double diffusion, the hollow spinning filament solidifies into primary fibers. The primary fibers are left standing at 75 °C for 2.5 h under vacuum conditions and dried at 55 °C for 7 h to obtain polystyrene hollow fibers; the polystyrene hollow fibers are woven into an electromagnetic shielding fabric through a textile machine. The remaining steps are the same as those in Example 2.
[0051] Comparative Example 2
[0052] The preparation method of the electromagnetic shielding fabric of Comparative Example 2 is different from that of Example 2 in that step (2) is not carried out, and step (5) is modified as follows: Modify polystyrene, magnesium hydroxide, phosphorus-silicon synergistic flame retardant, chloroplatinic acid, and N,N-dimethylformamide are mixed evenly according to a mass ratio of 1:0.05:0.07:0.0015:6.5, stirred at 20 °C and 400 r / min for 15 min to prepare a spinning solution; the spinneret is immersed in deionized water, the spinning solution is poured into the liquid container for wet spinning, and the spinning solution in the liquid container is transported to the spinneret assembly through a peristaltic pump at a transport speed of 0.6 mL / min. The outer diameter of the spinneret holes on the spinneret is 1.4 mm, and the inner diameter is 0.7 mm. After the spinning solution is extruded through the spinneret holes, a hollow spinning filament is formed. At the same time, another peristaltic pump transports deionized water into the hollow spinning filament at a transport speed of 0.9 mL / min. The inner and outer surfaces of the hollow spinning filament are in contact with deionized water at the same time. Under the action of double diffusion, the hollow spinning filament solidifies into primary fibers. The primary fibers are left standing at 75 °C for 2.5 h under vacuum conditions and dried at 55 °C for 7 h to obtain polystyrene hollow fibers; the polystyrene hollow fibers are woven into an electromagnetic shielding fabric through a textile machine. The remaining steps are the same as those in Example 2.
[0053] Comparative Example 3
[0054] The preparation method of the electromagnetic shielding fabric of Comparative Example 3 is different from that of Example 2 in that steps (3) and (4) are not carried out, and step (5) is modified as follows: Polystyrene, polycarbazole-coated magnesium hydroxide, phosphorus-silicon synergistic flame retardant, chloroplatinic acid, and N,N-dimethylformamide are mixed evenly according to a mass ratio of 1:0.05:0.07:0.0015:6.5, and stirred at 20 °C and 400 r / min for 15 min to prepare a spinning solution; The spinneret is immersed in deionized water, the spinning solution is poured into the liquid container for wet spinning, and the spinning solution in the liquid container is transported to the spinneret assembly through a peristaltic pump at a transport speed of 0.6 mL / min. The outer diameter of the spinneret holes on the spinneret is 1.4 mm, and the inner diameter is 0.7 mm. After the spinning solution is extruded through the spinneret holes, a hollow spinning filament is formed. At the same time, another peristaltic pump transports deionized water into the hollow spinning filament at a transport speed of 0.9 mL / min. The inner and outer surfaces of the hollow spinning filament come into contact with deionized water at the same time. Under the action of double diffusion, the hollow spinning filament solidifies into a primary fiber. The primary fiber is left standing at 75 °C for 2.5 h under vacuum conditions and dried at 55 °C for 7 h to obtain polystyrene hollow fibers; The polystyrene hollow fibers are woven into an electromagnetic shielding fabric through a textile machine. The remaining steps are the same as those in Example 2.
[0055] Test Example 1
[0056] Test of Flame Retardancy Performance
[0057] Test method: According to GB / T5454 "Textiles - Burning Performance - Oxygen Index Method", the limiting oxygen index of the examples and comparative examples was tested using an oxygen index instrument. The results are shown in Table 1.
[0058] Table 1
[0059] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 33.75 Comparative Example 1 25.45 Example 2 34.27 Comparative Example 2 28.36 Example 3 33.28 Comparative Example 3 33.16
[0060] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 1, it can be found that the electromagnetic shielding fabric prepared by the present invention has good flame retardancy performance.
[0061] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that a phosphorus-containing flame retardant monomer is prepared by reacting 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide with formic acid; the carbon-carbon double bond on tetramethyldivinyldisiloxane and the P-H bond on the phosphorus-containing flame retardant monomer are subjected to a hydrophosphination reaction to prepare a phosphorus-silicon synergistic flame retardant; phosphorus elements can capture free radicals, promote the formation of a carbon layer to isolate heat and oxygen, and endow the electromagnetic shielding fabric with excellent flame retardant properties; the bond energy of the Si-O bond is greater than that of the C-C bond, so compared with the C-C bond, the Si-O bond needs to absorb more heat and its own vibration energy to resolve the energy for the thermal decomposition of the polymer material. The layered SiO formed by the degradation of the siloxane during combustion migrates to the surface of the carbon layer, making the carbon layer more dense, inhibiting the oxidation of the carbon layer, enhancing the stability of the carbon layer at high temperatures, and further improving the flame retardant properties of the electromagnetic shielding fabric. 2 Migrates to the surface of the carbon layer, making the carbon layer more dense, inhibiting the oxidation of the carbon layer, enhancing the stability of the carbon layer at high temperatures, and further improving the flame retardant properties of the electromagnetic shielding fabric.
[0062] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 2, indicating that polycarbazole-coated magnesium hydroxide is prepared by oxidatively polymerizing carbazole and N-vinylcarbazole and depositing them on the surface of magnesium hydroxide; magnesium hydroxide has an endothermic effect. When magnesium hydroxide is heated by a heat source, it will undergo a dehydration reaction to generate water vapor and magnesium oxide. This is an endothermic reaction that absorbs a large amount of heat. Magnesium oxide will react with the carbide on the surface of the combustible to form a stable carbide layer. This carbide layer has good heat insulation performance and can prevent the combustible from contacting with external oxygen. The surface modification of magnesium hydroxide is carried out to improve the compatibility of magnesium hydroxide with the matrix resin, so that magnesium hydroxide is not easily agglomerated in the group resin and is evenly dispersed, further improving the flame retardant properties of the electromagnetic shielding fabric.
[0063] Test Example 2
[0064] Testing of antibacterial properties
[0065] Test method: The antibacterial rate is calculated by comparing the number of colonies of Escherichia coli cultured on agar medium for 16 h by the shaking method GB / T 20944.3, so as to analyze the antibacterial properties of the examples and comparative examples. The results are shown in Table 2.
[0066] Table 2
[0067] Bacteriostatic rate (%) Bacteriostatic rate (%) Example 1 99.89 Comparative Example 1 99.72 Example 2 99.92 Comparative Example 2 99.76 Example 3 99.86 Comparative Example 3 70.17
[0068] It can be found from the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2 that the electromagnetic shielding fabric prepared by the present invention has good antibacterial properties.
[0069] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 3, indicating that salicylaldehyde tyrosine Schiff base ligand is prepared by reacting 3-allyl-2-hydroxybenzaldehyde with tyrosine; the organotin antibacterial agent is prepared by reacting salicylaldehyde tyrosine Schiff base ligand with dimethyltin dichloride, introducing hydroxyl groups and carbon-carbon double bonds at both ends of the organotin antibacterial agent respectively; pre-modified polystyrene is prepared by reacting polystyrene with chloromethyl methyl ether, partially chloromethylating the benzene ring on polystyrene and introducing chlorine atoms on the side chain of polystyrene, and reacting the chlorine atoms on the pre-modified polystyrene with the hydroxyl groups on the organotin antibacterial agent to obtain modified polystyrene; the organotin antibacterial agent is grafted on the side chain of the modified polystyrene; the organotin complex on the organotin antibacterial agent can effectively inhibit the biological activity of bacteria and endow the electromagnetic shielding fabric with excellent antibacterial properties.
[0070] Test Example 3
[0071] Test of electromagnetic shielding performance
[0072] Test method: The electromagnetic shielding effectiveness values of the examples and comparative examples were tested according to GB / T 30139. The results are shown in Table 3.
[0073] Table 3
[0074]
[0075] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 3, it can be found that the electromagnetic shielding fabric prepared by the present invention has good electromagnetic shielding performance.
[0076] By comparison, the electromagnetic shielding effectiveness values of Examples 1 to 3 are greater than that of Comparative Example 2, indicating that polycarbazole-coated magnesium hydroxide is prepared by oxidatively polymerizing and depositing carbazole and N-vinylcarbazole on the surface of magnesium hydroxide; polycarbazole is a conductive polymer material, which can form a conductive path in the electromagnetic shielding fabric and endow the electromagnetic shielding fabric with excellent electromagnetic shielding performance.
[0077] Test Example 4
[0078] Test of mechanical properties
[0079] Test method: The mechanical properties of the polystyrene hollow fibers prepared in the examples and comparative examples were tested by using an XL-1A type filament strength and elongation tester. The test specimen was passed around the yarn guide hook and yarn guide wheel, and passed through the upper and lower holders downward to ensure that the test specimen was straightened without slack. A pre-tension of about 10 cN was applied to the test specimen. When the lower holder drove the test specimen to move downward until the test specimen broke and then returned to the original position, the breaking strength of the test specimen was obtained. The clamping distance was 250 mm, the stretching speed was 250 mm / min, and each test specimen was repeated more than 10 times. The test results were averaged. The results are shown in Table 4.
[0080] Table 4
[0081] Breaking strength (cN / dtex) Breaking strength (cN / dtex) Example 1 5.62 Comparative Example 1 3.01 Example 2 5.73 Comparative Example 2 4.23 Example 3 5.68 Comparative Example 3 4.03
[0082] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-3 in Table 4, it can be found that the electromagnetic shielding fabric prepared by the present invention has good mechanical properties.
[0083] By comparison, the breaking strength of Examples 1-3 is greater than that of Comparative Example 1, indicating that a phosphorus-containing flame retardant monomer is prepared by reacting 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide with formic acid, and P-H bonds are introduced at both ends of the phosphorus-containing flame retardant monomer; the carbon-carbon double bond on tetramethyldivinyldisiloxane reacts with the P-H bond on the phosphorus-containing flame retardant monomer by phosphine-hydrogen addition reaction to prepare a phosphorus-silicon synergistic flame retardant, keeping the phosphorus-containing flame retardant monomer in excess, so that both ends of the phosphorus-silicon synergistic flame retardant are capped with the phosphorus-containing flame retardant monomer, and P-H bonds are introduced at both ends of the phosphorus-silicon synergistic flame retardant; the P-H bonds introduced at both ends of the phosphorus-silicon synergistic flame retardant can react with the carbon-carbon double bonds on polycarbazole-coated magnesium hydroxide and modified polystyrene by phosphine-hydrogen addition reaction to form a crosslinked network, inhibit the relative slippage between molecular chains, and endow the electromagnetic shielding fabric with excellent mechanical properties.
[0084] By comparison, the breaking strength of Examples 1-3 is greater than that of Comparative Example 2, indicating that polycarbazole-coated magnesium hydroxide is prepared by oxidatively polymerizing carbazole and N-vinylcarbazole and depositing it on the surface of magnesium hydroxide; and carbon-carbon double bonds are introduced on the surface of polycarbazole-coated magnesium hydroxide; the carbon-carbon double bonds introduced on the surface of polycarbazole-coated magnesium hydroxide can react with the P-H bonds introduced at both ends of the phosphorus-silicon synergistic flame retardant by addition reaction to form a crosslinked network, inhibit the relative slippage between molecular chains, and endow the electromagnetic shielding fabric with excellent mechanical properties.
[0085] By comparison, the breaking strength of Examples 1-3 is greater than that of Comparative Example 3, indicating that salicylaldehyde tyrosine Schiff base ligand is prepared by reacting 3-allyl-2-hydroxybenzaldehyde with tyrosine; an organotin antibacterial agent is prepared by reacting the salicylaldehyde tyrosine Schiff base ligand with dimethyltin dichloride, and hydroxyl groups and carbon-carbon double bonds are introduced at both ends of the organotin antibacterial agent respectively; pre-modified polystyrene is prepared by reacting polystyrene with chloromethyl methyl ether, the benzene ring on polystyrene is partially chloromethylated, chlorine atoms are introduced on the side chain of polystyrene, and the chlorine atoms on the pre-modified polystyrene react with the hydroxyl groups on the organotin antibacterial agent to prepare modified polystyrene; the organotin antibacterial agent is grafted on the side chain of the modified polystyrene, and carbon-carbon double bonds are introduced; the carbon-carbon double bonds on the side chain of the modified polystyrene can react with the P-H bonds introduced at both ends of the phosphorus-silicon synergistic flame retardant by addition reaction to form a crosslinked network, inhibit the relative slippage between molecular chains, and endow the electromagnetic shielding fabric with excellent mechanical properties.
[0086] Matters not described in the present invention are applicable to the prior art.
Claims
1. An electromagnetic shielding fabric, characterized in that: The electromagnetic shielding fabric is prepared by addition polymerization of tetramethyl divinyl disiloxane and phosphorus-containing flame retardant monomer to obtain phosphorus-silicon synergistic flame retardant; oxidative polymerization of carbazole and N-vinyl carbazole and deposition on the surface of magnesium hydroxide to obtain polycarbazole-coated magnesium hydroxide; pre-modified polystyrene and organic tin antibacterial agent are reacted to obtain modified polystyrene; modified polystyrene, polycarbazole-coated magnesium hydroxide and phosphorus-silicon synergistic flame retardant are prepared into spinning solution, and polystyrene hollow fibers are obtained by wet spinning; and the polystyrene hollow fibers are woven into electromagnetic shielding fabric; The phosphorus-containing flame retardant monomer is prepared by reacting 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide with formic acid; The organotin antibacterial agent is prepared by reacting salicylaldehyde tyrosine Schiff base ligand with dimethyltin chloride; The salicylaldehyde tyrosine Schiff base ligand is prepared by reacting 3-allyl-2-hydroxybenzaldehyde with tyrosine; The pre-modified polystyrene is prepared by reacting polystyrene with chloromethyl methyl ether.
2. A method for preparing an electromagnetic shielding fabric, characterized in that: The method comprises the following preparation steps: (1) Tetramethyldivinyldisiloxane and a phosphorus-containing flame retardant monomer are added in a molar ratio of 1:(1.1-1.3) to N,N-dimethylformamide (10-12 times the mass of tetramethyldivinyldisiloxane), and the mixture is stirred at 60-70° C. and 300-500 r / min for 10-12 hours under nitrogen protection, and then dried at 50-60° C. for 7-9 hours under vacuum conditions to obtain a phosphorus-silicon synergistic flame retardant; (2) Mixing magnesium hydroxide, anhydrous ferric chloride and dichloromethane in a mass ratio of 1:(2-3):(20-30) to prepare a mixed reaction liquid; adding carbazole and N-vinyl carbazole in a molar ratio of 1:(0.2-0.3) to dichloromethane with a mass of 8-10 times that of carbazole to prepare a carbazole monomer solution; adding the carbazole monomer solution with a mass of 0.4-0.6 times that of the mixed reaction liquid to the mixed reaction liquid at a uniform speed within 30 minutes at 20-30° C. and 300-500 r / min stirring conditions, continuing to stir and react for 20-24 hours, and drying at 50-60° C. under vacuum conditions for 7-9 hours to obtain polycarbazole-coated magnesium hydroxide; (3) Dimethyltin chloride and methanol are mixed uniformly at a mass ratio of 1:(4-6) to prepare a dimethyltin chloride solution; equal molar amounts of dimethyltin chloride, salicylaldehyde tyrosine Schiff base ligand, triethylamine, and methanol are mixed uniformly at a mass ratio of 1:(0.03-0.05):(8-10), and under nitrogen protection, at 50-60° C., 300-500 r / min stirring conditions, the dimethyltin chloride solution is added dropwise at a uniform speed within 10 minutes, and the stirring reaction is continued for 1-2 hours, and the organic tin antibacterial agent is prepared at 50-60° C. under vacuum conditions for 7-9 hours. (4) Pre-modified polystyrene, organotin antibacterial agent, potassium carbonate and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:(0.2-0.3):(0.02-0.04):(10-12), stirred at 55-65° C. and 300-500 r / min for 2-3 h, and dried at 50-60° C. under vacuum conditions for 8-10 h to obtain modified polystyrene; (5) Modified polystyrene, polycarbazole-coated magnesium hydroxide, phosphorus silicon synergistic flame retardant, chloroplatinic acid, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:(0.04-0.06):(0.06-0.08):(0.001-0.002):(6-7), and stirred at 10-30°C and 300-500 r / min for 10-20 min to prepare a spinning solution; the spinning solution is wet-spun to obtain spun fibers, the spun fibers are allowed to stand at 70-80°C under vacuum conditions for 2-3 h, and dried at 50-60°C for 6-8 h to obtain polystyrene hollow fibers; the polystyrene hollow fibers are spun into electromagnetic shielding fabrics using a textile machine.
3. The method for preparing an electromagnetic shielding fabric according to claim 2, characterized in that: The preparation method of the phosphorus-containing flame retardant monomer in step (1) is as follows: 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide and chloroform are uniformly mixed in a mass ratio of 1:(10-12); under nitrogen protection, at 20-40° C., under stirring conditions of 300-500 r / min, formic acid is uniformly added dropwise within 30 minutes with a molar amount of twice that of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide; the reaction is continued by stirring for 30-40 minutes; and the phosphorus-containing flame retardant monomer is obtained by drying at 50-60° C. for 6-8 hours under vacuum conditions.
4. The method for preparing an electromagnetic shielding fabric according to claim 2, characterized in that: The particle size of the magnesium hydroxide in step (2) is 1 to 2 μm.
5. The method for preparing an electromagnetic shielding fabric according to claim 2, characterized in that: The preparation method of the salicylaldehyde tyrosine Schiff base ligand in step (3) is as follows: 3-allyl-2-hydroxybenzaldehyde and methanol are uniformly mixed in a mass ratio of 1:(4-6) to prepare a 3-allyl-2-hydroxybenzaldehyde solution; 3-allyl-2-hydroxybenzaldehyde and tyrosine and potassium hydroxide in a molar ratio of 1:1 are added to methanol with a mass of 10 to 12 times that of tyrosine, and stirred at 50 to 60° C. and 300 to 500 r / min for 8 to 12 minutes; under nitrogen protection, 50 to 60° C. and 300 to 500 r / min stirring conditions, 3-allyl-2-hydroxybenzaldehyde solution is uniformly added dropwise within 15 minutes, stirring reaction is continued for 2 to 3 hours, and drying is performed at 50 to 60° C. under vacuum conditions for 7 to 9 hours to obtain the salicylaldehyde tyrosine Schiff base ligand.
6. The method for preparing an electromagnetic shielding fabric according to claim 2, characterized in that: The preparation method of the pre-modified polystyrene in step (4) is as follows: polystyrene, chloromethyl methyl ether, tin tetrachloride and N,N-dimethylformamide are uniformly mixed in a mass ratio of 1:(0.2-0.3):(0.03-0.05):(10-12), stirred at 30-40°C and 300-500r / min for 4-6h, and dried at 50-60°C under vacuum conditions for 8-10h to obtain the pre-modified polystyrene.
7. The method for preparing an electromagnetic shielding fabric according to claim 6, characterized in that: The molecular weight of the polystyrene is 90,000 to 100,000.
8. The method for preparing an electromagnetic shielding fabric according to claim 2, characterized in that: The process flow of wet spinning in step (5) is as follows: immersing the spinneret in deionized water, pouring the spinning solution into a wet spinning liquid container, and conveying the spinning solution in the liquid container to the spinneret assembly through a peristaltic pump at a conveying speed of 0.58 to 0.62 mL / min. The outer diameter of the spinneret hole on the spinneret is 1.3 to 1.5 mm, and the inner diameter is 0.6 to 0.8 mm. The spinning solution is extruded through the spinneret hole to form a hollow spinning stream. At the same time, another peristaltic pump conveys deionized water into the hollow spinning stream at a conveying speed of 0.8 to 1 mL / min. The inner and outer surfaces of the hollow spinning stream are in contact with the deionized water at the same time. Under the action of double diffusion, the hollow spinning stream is solidified into a primary fiber.